Analisis Daya Saing Ekonomi di Kabupaten Kepulauan Meranti - M Hamid (JIP ( Jurnal Industri dan Perkotaan ), 2022)
The research aims to analyze the variables that influence and determine the regional competitiveness of Kepulauan Meranti an it in 2019 using Analytical Hierarchy Process (AHP) method. The research used primary data with questionnaires and interviews with 40 respondents consisting of members of the Regency DPRD, sub-district heads, heads of government sections, Socio-Cultural and Village Community Empowerment. The research consists of five institutional variables; socio-political, regional labor, economy, productivity and physical infrastructure. The results of regional competitiveness among sub-districts are economic variables in the Tasik Putri Puyu sub-district’s (0.475), Tebing Tinggi subdistrict’s physical infrastructure (0.373), labor and productivity of Pulau Merbau sub-district (0.216), Rangsang Pesisir Barat sub-district’s high cliff institutions (0.260) and Rangsang Pesisir sub-district’s social politics (0.333).